2010
DOI: 10.1152/ajpendo.00738.2009
|View full text |Cite
|
Sign up to set email alerts
|

Sodium bicarbonate ingestion prior to training improves mitochondrial adaptations in rats

Abstract: We tested the hypothesis that reducing hydrogen ion accumulation during training would result in greater improvements in muscle oxidative capacity and time to exhaustion (TTE). Male Wistar rats were randomly assigned to one of three groups (CON, PLA, and BIC). CON served as a sedentary control, whereas PLA ingested water and BIC ingested sodium bicarbonate 30 min prior to every training session. Training consisted of seven to twelve 2-min intervals performed five times/wk for 5 wk. Following training, TTE was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 65 publications
6
63
2
1
Order By: Relevance
“…The hypothesis that training intensity may be an important determinant of improvements in mitochondrial respiration is consistent with the cross-sectional data (see Figure 1), and also three studies involving young, healthy rats (note: studies involving voluntary running, or aged or diseased rats were not included) [59][60][61]. While once again the number of studies is small, and there are many differences between the studies (e.g., type and sex of rat), there is a trend for greater increases in mitochondrial respiration with higher training intensities (Fig 2).…”
Section: Mitochondrial Functionsupporting
confidence: 79%
“…The hypothesis that training intensity may be an important determinant of improvements in mitochondrial respiration is consistent with the cross-sectional data (see Figure 1), and also three studies involving young, healthy rats (note: studies involving voluntary running, or aged or diseased rats were not included) [59][60][61]. While once again the number of studies is small, and there are many differences between the studies (e.g., type and sex of rat), there is a trend for greater increases in mitochondrial respiration with higher training intensities (Fig 2).…”
Section: Mitochondrial Functionsupporting
confidence: 79%
“…There is some evidence that bicarbonate supplementation during a period of high-intensity interval cycle ergometer training can enhance the mitochondrial adaptations taking place (Bishop et al, 2010) and can also improve performance (Edge et al, 2006). A more recent study involving well-trained rowers, however, did not find that bicarbonate supplementation during 4 weeks of high-intensity interval training provided any performance advantage over the placebo supplementation condition (Driller et al, 2013).…”
Section: Bicarbonate and Beta-alaninementioning
confidence: 99%
“…Using a systematic mock-up of a stomacher, described above, it was shown that Kre-Alkalyn maintained a significantly higher pH than traditional creatine, in three separate reagents tested. A slow decline from highly basic pH (12) to neutral pH (7) after 45 minutes with KreAlkalyn in a 0.1 M HCl solution was observed. Even with the addition of hydrogencarbonate/sodium carbonate or ethanolamine/ethanolamine hydrochloride, commonly used biopharmaceutical buffers, which increased the rate of pH reduction, Kre-Alkalyn maintained higher pH levels than traditional creatine?…”
Section: Resultsmentioning
confidence: 97%
“…Though understudied in the context of creatine, changes in acid-base regulation have also been shown to effect protein-protein interactions [11], mitochondrial efficiency [12], and cellular signaling and proliferation [13,14]. Furthermore, Kre-Alkalyn increased cytoprotection against cisplatin-induced cytotoxicity compared to conventional creatine in 293 T human kidney cells [8], suggesting another possible utility of in vivo creatine buffering.…”
Section: Introductionmentioning
confidence: 99%